Peripheral Giant Cell Granuloma: A Case Report - Ghimire, N; Nepal, P; Ghimire, N (Journal of Chitwan Medical College, 2013)
Peripheral giant cell granuloma is a benign reactive lesion of gingiva. It manifests as a firm, soft, bright nodule, sessile or pedunculate mass. It is an infrequent exophytic lesion of the oral cavity, also known as giant cell epulis, osteoclastoma, giant cell reparative granuloma, or giant-cell hyperplasia. The aim in publishing this report is to present the clinical, histopathological features and treatment of a peripheral giant cell granuloma case, which was seen in gingiva of a 10 year old male child, with history of disturbed chewing functions due to its large size. Intraoral examination revealed a raised, round, sessile, smooth-edged mass of size 2x 1 cm2 and was located on the canine, deciduous first molar region. After initial periodontal treatment, excisional biopsy was performed under local anesthesia. The lesion was diagnosed as Peripheral Giant Cell Granuloma after clinical and pathological examination. DOI: http://dx.doi.org/10.3126/jcmc.v3i3.8635 Journal of Chitwan Medical College 2013; 3(3): 28-30